ANALYSIS OF HOW LEARNING ENVIRONMENT PARAMETERS IMPACT CHILD SAFETY - Tsevelmaa Demberel (International Journal of Innovative Technologies in Social Science, 2025)
This study aimed to assess the current state of the learning environment for children in Mongolia and evaluate the impact of policy and legal frameworks. The study involved 1,025 school-age children from 12 aimags, 9 districts, and 5 districts in 21 provinces, and utilized primary and qualitative data analysis. The findings revealed that the overall environment surrounding children (including school, family, society, individual, and community) significantly influences the safety of the learning environment. However, the study identified weak social and community support at the local level, inadequate internal security within families, and insufficient safety measures in school environments. It also highlighted the inadequate implementation of policies aimed at ensuring child safety. The study emphasized the need for effective coordination of laws, budgets, and initiatives to enhance the internal environment of schools. This research provides essential baseline data for policymakers and researchers to enhance child safety, promote school and community involvement, and improve the learning environment.